MANAJEMEN PROGRAM LAYANAN BIMBINGAN KONSELING DI MAS PONDOK PESANTREN RAUDHATUSSALAM MAHATO - Wahyuni, Dwi (UNISAN JURNAL, 2025)
This journal discusses the management of guidance and counseling services programs at Madrasah Aliyah Sumber Raudhatussalam Mahato. The main focus of this research is to identify the structure, processes, and evaluation of existing programs, as well as how these programs face challenges in implementation. This research was conducted using a qualitative approach, with data collection through interviews, observations, and documentation. The findings reveal that the counseling guidance program at this boarding school has been functioning well but still needs optimization in the aspects of human resource management and facilities. The use of technology in counseling services was also found to be underutilized. The results of this study are expected to contribute to the development of counseling management in pesantren-based educational institutions and provide recommendations for improvement. Keywords: Management, counseling services, Islamic boarding school, Raudhatussalam, education.